It's all about the text: An experimental investigation of inconsistent reviews on restaurant booking platforms - Andreas J. Steur; Fabian Fritzsche; Mischa Seiter (Electronic Markets, 2022)
Consumer-generated reviews play a decisive role in creating trust and facilitating transactions on digital platforms. However, prior research shows various problems, e.g., only a small number of consumers providing reviews, fake reviews, and inconsistent reviews. We use an experiment in the context of a restaurant booking platform to examine the impact of inconsistent reviews on the duration of consumers' transaction decisions. In a second experiment, we investigate the relative importance of the review components in the case of inconsistent reviews. Drawing on the dual-process theory and media richness theory, we predict that inconsistent reviews result in a longer time required for consumers' transaction decisions (H1) and lead to users' transaction decisions being predominantly based on the qualitative component (H2). Although we do not find general support that inconsistent restaurant reviews negatively determine the duration of transaction decisions, we find evidence that in the case of inconsistent restaurant reviews, the polarity of the qualitative component is crucial for both the duration of the transaction decision and the decision itself.
Keywords: M31; 620; Consumer reviews; Online reviews; Inconsistent reviews; Reputation; Digital platform; Consumer decision-making